The performance of limestone filter with horizontal subsurface flow (HSF) wetland in landfill treatment - Nursyiqah, Jasman (2013)
The effect of limestone filter with wetland in landfill leachate treatment was studied. The combination of these two systems was seen as a good way to eliminate organic and inorganic matters in wastewater because limestone filter offers an abiotic condition while wetland offers a biotic condition. Control system (limestone filter) and fulltreatment system (limestone filter with HSF wetland) were used in this study. Before and after treatments concentrations of parameters for pH, COD, BOD, TSS, NH3—N, oil and grease, lead (Pb), zinc (Zn), manganese (Mn), iron (Fe) and copper (Cu) in leachate taken from Jabor-Jerangau Landfill were studied in a continuous flow mode. The sample was pre-treated with aeration beforehand for 48 hours. The filter was filled with limestone of sizes 2mm, 5mm, 10mm and 14mm that were layered in ascending order from top to bottom with ratio 30:25:25:20. Horizontal subsurface flow (HSF) system was applied to the wetland. From the result generated, it was found that combination of limestone with HSF wetland shows higher average percentage removal with 72.5% COD, 42.9% BOD, 73% TSS, 68.3% NH3—N, 62% oil and grease, 79% lead, 82.2% manganese and 40.6% zinc. Both systems have the same breakpoint which was at 12day HRT. This study concludes that full-treatment system can improve leachate quality and has good efficiency within 12 days.